Strategic Management Of The Final Project Program In Improving Students' Writing Skills - Novienda, Ulfa Dina; Azizah, Nur; Awakachi, Arfal (The Faculty of Education and Teaching Training, 2025)
In today's era, writing skills are very important in conveying messages and information to others indirectly. Writing skills are very much needed in both academic and non-academic contexts. With this writing activity, it really expands the reach of communication between writers and readers which is not only for one period with the writer, but can continue for future layers of readers. The purpose of the researcher in this study is to describe the Implementation of the Final Assignment program strategy to improve students' writing skills in class XI students, secondly to describe the evaluation of the Final Assignment program to improve students' writing skills in class XI students at SMA Tunas Luhur Paiton Probolinggo. This study uses qualitative research with the type of research (field research) field research. Data collection techniques use observation, interviews and documentation. Regarding data analysis using the theory of Miles Huberman and Saldana, namely data collection, data condensation, data presentation, and drawing conclusions. Data validity uses source triangulation and technique triangulation. The results of this study can be concluded that 1) the formulation of strategies carried out at SMA Tunas Luhur related to the TA program consists of planning where in this planning it is conveyed in work meeting activities related to the planning of the formulation of the Final Assignment program strategy which is carried out every six months., determining the vision and mission, and SWOT analysis, 2) in the implementation of the Final Assignment program management strategy carried out at SMA Tunas Luhur Paiton, there are organizing, actuating, and controlling. 3) For the evaluation of the Final Assignment program carried out at SMA Tunas Luhur Paiton, namely input evaluation, process evaluation, and outcome evaluation